Poverty, gender and life-cycle under the English poor law, 1760-1834 - Williams, Samantha, 1970- (Royal Historical Society studies in history. New series., 2011)
Social welfare, increasingly extensive during the seventeenth and eighteenth centuries, was by the first third of the nineteenth under considerable, and growing, pressure, during a "crisis" period when levels of poverty soared. This book examines the poor and their families during these final decades of the old Poor Law. It takes as a case study the lived experience of poor families in two Bedfordshire communities, Campton and Shefford, and contrasts it with the perspectives of other participants in parish politics, from the magistracy to the vestry, and from overseers to village rat.